2017
DOI: 10.3758/s13415-016-0487-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates reflect the integration of model-based and model-free decision information

Abstract: In this study, we investigated the interplay of habitual (model-free) and goal-directed (model-based) decision processes by using a two-stage Markov decision task in combination with event-related potentials (ERPs) and computational modeling. To manipulate the demands on model-based decision making, we applied two experimental conditions with different probabilities of transitioning from the first to the second stage of the task. As we expected, when the stage transitions were more predictable, participants sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 59 publications
11
46
1
Order By: Relevance
“…By contrast, Experiment 1 in our study eliminated the RPE/SPE confound in the two-step task by removing the reward element, which revealed a robust SPE. Similarly, Eppinger et al (2017) reported an effect of transition type on the LPC that replicates our ERP findings reported in the SOM, though their effect was considerably smaller (dz=0.48) relative to that of our study (dz=1.17; supplementary online material). In summary, whereas our findings do not generally disagree with the previous results, ours is the first to report that SPEs elicit a robust FMT response and elevated delta levels that correlate with behavioral adjustments.…”
Section: Discussionsupporting
confidence: 87%
“…By contrast, Experiment 1 in our study eliminated the RPE/SPE confound in the two-step task by removing the reward element, which revealed a robust SPE. Similarly, Eppinger et al (2017) reported an effect of transition type on the LPC that replicates our ERP findings reported in the SOM, though their effect was considerably smaller (dz=0.48) relative to that of our study (dz=1.17; supplementary online material). In summary, whereas our findings do not generally disagree with the previous results, ours is the first to report that SPEs elicit a robust FMT response and elevated delta levels that correlate with behavioral adjustments.…”
Section: Discussionsupporting
confidence: 87%
“…Previous EEG studies of the two-step task (Eppinger et al, 2017;Sambrook et al, 2018;Shahnazian et al, 2019) showed that the P300 was associated with state transitions. However, the inconsistent direction on the effects raises doubt as to how these differences should be interpreted.…”
Section: Discussionmentioning
confidence: 95%
“…Participants have to take into consideration the task transition structure and their history of rewards to make choices that maximise reward. The sequence of events as presented for EEG is the same as that of Eppinger et al (2017), except they included a manipulation of transition probabilities in their study (comparing 60/40% to 80/20%) and used a longer choice window (2000ms).…”
Section: Figure 1 Two-step Reinforcement Learning Task Paradigm Conmentioning
confidence: 99%
See 1 more Smart Citation
“…In value-based decision making, the P3 is part of feedback processing 25,27,49 , and shows sensitivity to reward magnitude, valence and probability/risk [50][51][52][53][54][55][56][57][58] . As in perceptual studies, the feedback P3 may reflect update and storage of reward values for behavioral adjustment 25,[59][60][61][62] , by integrating them with internal models of a probabilistic task 63 . It may similarly reflect reward evidence accumulation dynamics 64 , possibly as a decision variable for strategic choice 65 .…”
Section: Value-based Feedback Erp Components Relevant To the Ipdmentioning
confidence: 99%